The Challenges of Hospitals’ Planning & Control Systems: The Path toward Public Value Management - Nuti, Sabina (Int J Environ Res Public Health, 2021)
In the last decades, public management has been subjected to a shift from the New Public Management (NPM) paradigm to the Public Value Management (PVM) one. Thus, management practices such as Planning and Control (P&C) systems have been called to evolve accordingly. The health care sector has not escaped this process. This paper focuses on the evolution of hospitals’ P&C systems to support the paradigm shift from the NPM paradigm to the PVM one. In particular, the paper aims at exploring whether hospitals’ P&C systems in Italy evolved, or are evolving, consistently with PVM and what are the expected benefits related to such a paradigm switch. To address the research aim, the paper is based on a review of scientific and grey literature and the case study of the diabetic-foot pathway in an Italian Regional Healthcare System. The results of this study show that the current P&C systems in Italian hospitals are not yet designed to support the shift toward the PVM approach and are still mainly focused on financial aspects and intra-organizational dynamics. Combining traditional P&Cs with performance measures assessing the system’s outcomes may support hospitals in aligning their goals with the health system they are operating within and, therefore, P&C systems may represent an important driving force toward change. Such results provide suggestions for both practitioners and academics on how to adapt P&C systems to better support the implementation of current strategies of the public sector.